Party manifestos, opposition and media as determinants of the cabinet agenda - Borghetto, E. (2022)
Cabinets are the engine of policy change in parliamentary systems. Yet we still know little about how cabinets micro-manage the content of their multifaceted agenda during their term in office. Drawing on the party and agenda-setting literature, this article addresses this gap by focusing on three main determinants of cabinet priorities: issue priorities in the electoral platforms of majority and opposition parties, and new and unforeseen problems as conveyed by the media. Our analysis reveals that: 1) as expected by the party agenda hypothesis, majority platforms have a stronger impact on the cabinet agenda than those of opposition parties, but this effect decreases as the legislative term progresses; 2) cabinet agendas do take into consideration opposition electoral priorities but only when the latter are expressed by mainstream competitors or when the media focus on them; 3) an externally-imposed adjustment programme can also create conditions for strengthening the congruence between electoral and cabinet agendas. This article furthers the understanding of the mechanisms used by cabinets for their regular agenda-setting through an analysis of the policy content of the Council of Ministers' press releases in Portugal from 1995 until 2015.